ANALISIS KINERJA MASYARAKAT PEMBUDIDAYAAN IKAN LELE DI DESA SUKAJADI KECAMATAN LIRIK KABUPATEN INDRAGIRI HULU - Tamara, Rizky; Wilson, Wilson; Jas, Jasfar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is motivated by the performance of catfish farmers. The formulation of this research problem is whether the performance analysis of the catfish culture community in Sukajadi Village Lirik District Indragiri Hulu Regency is good ?. The purpose of this study was to determine the performance of catfish farmers in Sukajadi Village Lirik District Indragiri Hulu Regency classified as good or bad. The expected benefits of the results of the study are to increase the knowledge and insight of the author and reader about the analysis of the performance of the catfish culture community and applying existing theories. The population in this study were 50 people of catfish farmers. Then the sample of this study was 50 people and 20 people in other places, namely in Gudang Batu Village, the sample used was saturated sample. The instrument of data collection was a questionnaire with 70 items of questions and after the trial only 68 items were valid questions to be used as research instruments. Data analysis through quantitative descriptive analysis. The findings of this study indicate that the catfish culture community has a good view of planning in cultivating catfish, the purpose of which has been done correctly. So that the best indicator of planning is compared to indicators of organizing, directing and controlling.Key Words: Performance Analysis, Analysis Of Community Performance